Jersey boys [videorecording (DVD)] - Walken, Christopher, 1943-; Schirripa, Steven R.; Young, John Lloyd; Piazza, Vincent. (Vincent Francis), 1976-; Bergen, Erich, 1985-; Lomenda, Michael (distributed by Warner Home Video, 2014)
The story of four young men from the wrong side of the tracks in New Jersey who came together to form the iconic 1960s rock group The Four Seasons.